The Influence of Social Media on Consumer Purchasing Decisions: Case Study of a Syar'i Clothing Stores - Tri Sugiarti Ramadhan; Sudarmiatin Sudarmiatin (International Journal of Economics, Business and Innovation Research, 2024)
With the rapid advancement of technology, the use of the internet has become commonplace in marketing products. E-marketing, or electronic marketing, is a subset of e-commerce that involves the communication, promotion, and sale of goods or services over the internet. Promotion strategies through the internet, especially by using social media, can increase sales without large marketing costs. Consumers can easily find information about products without having to interact directly. This allows consumers to be more interested in buying through social media, as is done by the Laila Ghani Muslim fashion store in marketing Muslim clothing, even though it still has physical outlets. This study aims to determine the direct and indirect effects of promotion through social media on consumer purchasing decisions for Laila Ghani Syar'i brand Muslim clothing products in Malang City, using quantitative methods with 70 respondents and path analysis. The results showed that the promotion carried out by Laila Ghani Syar'i in Malang City both directly and indirectly through social media had a significant influence on consumer purchasing decisions on syar'i clothing products.